PENANAMAN NILAI-NILAI HAK ASASI MANUSIA DALAM TRADISI PONDOK PESANTREN: STUDI KASUS SANTRI PONDOK PESANTREN NURUL JADID - Adjimaulin, Syarafina (Universitas Nurul Jadid, 2024)
The Qur'an as a guide and guidance for the life of Muslims, has regulated all life values that are the basic rights of every person. Instilling human rights values is one form of adaptation to the demands of the times, as well as an effort to realize social harmony in community life. The tradition of Islamic boarding schools in Indonesia, as one of the oldest Islamic educational institutions, has a strategic role in shaping individual character through teaching religion, local culture, and universal morals. This article discusses how Islamic boarding schools internalize human rights values in educational practices and daily life, with an emphasis on the principles of justice, respect for differences, and balance between rights and obligations. Through a historical and normative approach, this study found that human rights values are often in line with Islamic teachings taught in Islamic boarding schools, although their application requires the right context and understanding. This integration is carried out through a yellow book-based learning method, a tradition of deliberation, and strengthening morals, which are the characteristics of Islamic boarding schools. This study confirms that the tradition of Islamic boarding schools has great potential in advancing human rights contextually, especially in a pluralistic society like Indonesia.